Evaluation of the effect of Modafinil in the improvement of the level of consciousness in patients with COVID‐19 encephalopathy: A randomized controlled trial - Fatemeh Talebi Kiasari; Mobin Naghshbandi; Maziar Emamikhah; Omid Moradi Moghaddam; Mohammad Niakan Lahiji; Mohammad Rohani; Narges Yazdi; Hamidreza Movahedi; Alireza Amanollahi; Pardis Irandoost; Roya Ghafoury (Wiley, 2024)
Abstract Aim COVID‐19 can lead to encephalopathy and loss of consciousness. This double‐blinded randomized clinical trial conducted in Tehran, Iran, aimed to assess the potential effectiveness of modafinil in patients with COVID‐19‐related encephalopathy. Methods Nineteen non‐intubated COVID‐19 patients with encephalopathy were randomized into two groups: a treatment group receiving crushed modafinil tablets and a placebo group receiving starch powder. Modafinil was administered at a dose of 100 mg every 2 h, reaching a peak dosage of 400 mg. The level of consciousness was assessed using the Glasgow Coma Score (GCS) at multiple time points on the day of medication administration. The trial was registered under IRCT20170903036041N3 on 23/5/2021. Results The average age in the modafinil and placebo groups was 75.33 and 70 years, respectively. No significant differences were observed between the two groups in terms of chronic conditions, clinical symptoms, or laboratory data. GCS scores were similar between the groups at baseline (p‐value = 0.699). After four doses of modafinil, GCS scores were slightly higher in the treatment group, but this difference was not statistically significant (p‐value = 0.581). GCS scores after each round of drug administration didn't significantly differ between the treatment and placebo groups (p‐value = 0.908). Conclusion Modafinil exhibited a slight improvement in the level of consciousness among COVID‐19 patients with encephalopathy, although this improvement did not reach statistical significance when compared to the control group. Further research with larger sample sizes and longer treatment durations is recommended to explore modafinil's potential benefits in managing altered consciousness in COVID‐19 patients.